2017
DOI: 10.1002/pc.24649
|View full text |Cite
|
Sign up to set email alerts
|

Design of doum palm fibers biocomposites by Reactor/elongational flow MiXer: Evaluation of morphological, mechanical, and microstructural performances

Abstract: An innovative mixing device RMX (Reactor/elongational flow MiXer), based on an elongational flow, is used to formulate new biocomposites based on Doum palm fiber (at various proportions) and PLA polymer. Due to its high elongational flow, RMX has the ability to mix immiscible products and to disperse the solid phase (fiber) in the viscous phase. The morphological aspect of PLA/Palm composites shows a good appearance and high fiber orientation and dispersive efficiency as confirmed by X‐ray tomography. For high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In this context, Samouh et al prepared biocomposites by incorporating sisal fibers to a PLA matrix and concluded that the increase in the rate of reinforcement improves the mechanical and dynamic mechanical properties and favors the PLA crystallinity due to the nucleating effect of the sisal fibers. Also, PLA biocomposites with ameliorated performances have been prepared from several natural fibers namely hemp, Doum palm, coir, flax, jute, and wood …”
Section: Introductionmentioning
confidence: 99%
“…In this context, Samouh et al prepared biocomposites by incorporating sisal fibers to a PLA matrix and concluded that the increase in the rate of reinforcement improves the mechanical and dynamic mechanical properties and favors the PLA crystallinity due to the nucleating effect of the sisal fibers. Also, PLA biocomposites with ameliorated performances have been prepared from several natural fibers namely hemp, Doum palm, coir, flax, jute, and wood …”
Section: Introductionmentioning
confidence: 99%
“…When the synergy angle α becomes zero, the flow is a pure elongational one, and if it becomes 90°, the flow is a pure shear one. Most notably, it is generally known that the effect of elongational flow on mixing is more strong than that of shear flow [19][20][21][22][23][24], which provides evidence for the feasibility of field synergy analysis. Therefore, the synergy relationship provides a new perspective to understand the polymer mixing.…”
Section: Synergy Between Velocity and Velocity Gradientmentioning
confidence: 99%
“…Polylactic acid (PLA) filled with natural fibers could provide excellent biocomposites for packaging purposes thanks to their renewable resources, biodegradability, low cost, and nontoxicity 4 . Accordingly, PLA has been reinforced by several natural fibers, such as jute, 4 Doum palm, 5 and kenaf 6 . Also, Sponge Gourd fibers, commonly known as luffa fibers (LFs), have been incorporated into PLA to prepare fully biodegradable composites.…”
Section: Introductionmentioning
confidence: 99%
“…4 Accordingly, PLA has been reinforced by several natural fibers, such as jute, 4 Doum palm, 5 and kenaf. 6 Also, Sponge Gourd fibers, commonly known as luffa fibers (LFs), have been incorporated into PLA to prepare fully biodegradable composites. In presence of MA grafted polylactic acid (PLA-g-MA), acting as a compatibilization promoter, the composites Izod impact strength increased relatively to the uncompatibilized counterparts, especially for 1 phr of LF, whereas water uptake aptitude and thermal stability were considerably reduced.…”
Section: Introductionmentioning
confidence: 99%